2017
DOI: 10.1002/2211-5463.12253
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive protein detection by biospecific AFM‐based fishing with pulsed electrical stimulation

Abstract: We report here the highly sensitive detection of protein in solution at concentrations from 10 –15 to 10 –18 m using the combination of atomic force microscopy ( AFM ) and mass spectrometry. Biospecific detection of biotinylated bovine serum albumin was carried out by fishing out the protein onto the surface of AFM chips with immobilized avidin, which determined the specificity of the analysis. Electrical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…These systems use an approach based on the introduction of an aqueous solution of an analyte (protein or virus) through an injector using either a pipette or flow system into a measuring cell containing a nanochip; analyte particles are captured onto the nanochip surface (i.e., fishing of the analyte occurs), where they are registered with molecular detectors in counting mode. In our previous paper [6] it was reported that by using systems for AFM-based fishing (that is, the systems, in which protein particles are captured from a large volume onto a small area of a chip for an atomic force microscope) it is possible to detect proteins at femtomolar and subfemtomolar concentrations upon feeding the protein solution into the measuring cell using an injector. As one of the factors of such a high efficiency of protein detection, the effect of charge generation in the analyte solution during its flow through an injector is considered.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These systems use an approach based on the introduction of an aqueous solution of an analyte (protein or virus) through an injector using either a pipette or flow system into a measuring cell containing a nanochip; analyte particles are captured onto the nanochip surface (i.e., fishing of the analyte occurs), where they are registered with molecular detectors in counting mode. In our previous paper [6] it was reported that by using systems for AFM-based fishing (that is, the systems, in which protein particles are captured from a large volume onto a small area of a chip for an atomic force microscope) it is possible to detect proteins at femtomolar and subfemtomolar concentrations upon feeding the protein solution into the measuring cell using an injector. As one of the factors of such a high efficiency of protein detection, the effect of charge generation in the analyte solution during its flow through an injector is considered.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, according to Reference [2], in a nanobiosensor system for AFM-based fishing at femtomolar and subfemtomolar protein concentrations, we observed a tendency for it to increase the number of captured protein molecules with the increase in the charge generated upon injection of analyzed solution into a measuring cell. External pulsed voltage applied to the measuring cell, was previously used by us to induce electric fields in flow-based systems for AFM-based fishing in order to enhance their sensitivity (up to the subfemtomolar level), as was demonstrated in Reference [6]. Thus, to enhance the efficiency of protein capturing in an AFM-based fishing system, it is important to study the phenomenon of charge generation during the flow of an aqueous solution through a flow-based system in various conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a triboelectric effect, described above, occurring upon the injection of a liquid with pipette tips, should also take place in nanotechnological highly sensitive atomic force microscopy (AFM)-based and nanowire biosensors, which are promising for the early diagnosis of diseases. In such biosensors, when an electric charge is generated in the supply system, it is supposed to play an important positive role in providing highly sensitive protein detection [2,28]. So, in [28], we demonstrated that a correlation is observed between the amount of protein, captured onto the sensor chip in the system for AFM-based fishing, and the charge generated per single protein particle.…”
Section: Introductionmentioning
confidence: 74%
“…Modern proteomic and biosensor systems (including chromato-mass-spectrometric and atomic force microscopy (AFM)-based ones, nanowire biosensors, etc.) allow one to detect proteins in water and water solutions with an ultra-high (10 −18 to 10 −15 M) concentration sensitivity [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%